Benjamin R. Young. 2021. Guns, Guerillas, and the Great Leader. North Korea and the Third World. Stanford: Stanford University Press. Ebook ISBN 9781503627642. https://doi.org/10.1515/9781503627642 - Aguirre Torrini, Camilo Sebastián (Estudios de Asia y África, 2021)
Benjamin R. Young. 2021. Guns, Guerillas, and the Great Leader. North Korea and the Third World. Stanford: Stanford University Press. Ebook ISBN 9781503627642. https://doi.org/10.1515/9781503627642